Effect of different complex carbon sources on growth and bacteriocin synthesis of Enterococcus faecium - Audisio, Marcela Carina (2001)
Different criteria are followed in order to select bacteria to be used in probiotic and symbiotic supplements. A new parameter to choose strains could be fermentation by intestinal bacteria of some complex carbohydrates because they are prebiotics and promote the development of beneficial microorganisms in the intestinal environment. An Enterococcus faecium strain, isolated from the crop of a free-range chicken, was assayed in order to determine the utilization of commercial sugars and/or crude carbohydrate samples from a sugar mill. The production of antimicrobial substances, under these conditions, was also considered. Ent. faecium CRL1385 grew well in the presence of complex carbohydrates and its ability to produce bacteriocin, active against poultry pathogens such as Ent. hirae, Salmonella pullorum and Listeria monocytogenes, was not significantly modified. These results are promising because the trend today is to employ eubiotic or symbiotic products and their use in the poultry industry could be a natural way to protect the flocks against potential pathogens.